Ion Migration and Space‐Charge Zones in Metal Halide Perovskites Through Short‐Circuit Transient Current and Numerical Simulations - Alvarez, Agustin O.; García‐Batlle, Marisé; Lédée, Ferdinand; Gros‐Daillon, Eric; Guillén, Javier Mayén; Verilhac, Jean‐Marie; Lemercier, Thibault; Zaccaro, Julien; Marsal, Lluis F.; Almora, Osbel; Garcia‐Belmonte, Germà (Advanced electronic materials, 2024)
The inherent ion migration in metal halide perovskite materials is known to induce deleterious and highly unstable dark currents in X‐ and γ‐ray detectors based on those compounds upon bias application. Dark current slow drift with time is identified as one of the major drawbacks for these devices to satisfy industrial requirements. Because dark current establishes the detectability limit, current evolution, and eventual growth may mask photocurrent signals produced by incoming X‐ray photons. Relevant information for detector assessment is ion‐related parameters such as ion concentration, ion mobility, and ionic space‐charge zones that are eventually built near the outer contacts upon detector biasing. A combined experimental (simple measurement of dark current transients) and 1D numerical simulation method is followed here using single‐crystal and microcrystalline millimeter‐thick methylammonium‐lead bromide that allows extracting ion mobility within the range of µion  ≈ 10−7 cm2 V−1 s−1, while ion concentration values approximate Nion ≈ 1015 cm−3, depending on the perovskite crystallinity. Dark current establishes the detectability limit in X‐ray perovskite‐based detectors. Ion migration induces current drift masking incoming photon‐produced photocurrent signals. Upon biasing, ionic accumulation and depletion space‐charge zones build up near the contacts modulating electronic carrier injection. Relevant parameters for the assessment of X‐ray detectors are accessible by a simple measurement of dark current transients and device simulation tools.